Effects of Cryopreservation on Gene Expression and Post Thaw Sperm Quality of Pacific Abalone, Haliotis discus hannai - Hossen, Shaharior; Sukhan, Zahid Parvez; Cho, Yusin; Kho, Kang Hee (Frontiers in Marine Science, 2021)
Pacific abalone, Haliotis discus hannai is a high commercial seafood in South-East Asia. The aim of the present study was to determine effects of cryopreservation on gene expression and post thaw sperm quality of Pacific abalone, H. discus hannai. Two ions, Na+ (459.1 ± 3.1 mM) and Cl- (515.9 ± 1.1 mM), were predominant in the seminal plasma (pH: 6.8 ± 0.1; osmolarity: 1126 ± 3 mOsmL-1). Cryopreservation reduced mRNA expression levels of protein kinase A (PKA-C) and heat shock proteins (HSP70 and HSP90) genes in sperm. Fluorescent technique was used to compare morphological defects, acrosome integrity (AI), plasma membrane integrity (PMI), mitochondrial membrane potential (MMP), and DNA integrity of sperm cryopreserved with five different cryopreservation solutions (8% Me2SO, 8% EG, 6% PG, 2% GLY, and 2% MeOH). Droplet in tail and coiled tail defects were not observed for sperm cryopreserved with 8% Me2SO or 2% GLY. Sperm cryopreserved with 8% Me2SO showed improved DNA integrity and lower cryodamage than sperm cryopreserved with other cryoprotectants. Sperm to egg ratio of 10000:1 was found to be the most suitable ratio for in vitro fertilization among different ratios tested. The fertilization rate of sperm cryopreserved with 8% Me2SO was not significantly (p > 0.05) different from that of sperm cryopreserved with 2% GLY. DNA fragmentation showed strongly negative relationships with sperm quality parameters. Sperm cryopreserved with 8% Me2SO showed higher post thaw quality and mRNA expression of sperm motility associated gene than those cryopreserved with other cryoprotectants. The present research suggests to use 8% Me2SO for cryopreservation of Pacific abalone sperm as well as for hatchery production.